Leucaena sp recombinant cinnamyl alcohol dehydrogenase: purification and physicochemical characterization - Patel, Parth; Gupta, Neha; Gaikwad, Sushama M.; Agrawal, Dinesh C.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2014)
Cinnamyl alcohol dehydrogenase is a broad substrate specificity enzyme catalyzing the final step in monolignol biosynthesis, leading to lignin formation in plants. Here, we report characterization of a recombinant CAD homologue (LICAD2) isolated from Leucaena leucocephala. LICAD2 is 80 kDa homodimer associated with non-covalent interactions, having substrate preference toward sinapaldehyde with K-cat/K-m of 11.6 x 10(6) (M-1 s(-1)), and a possible involvement of histidine at the active site. The enzyme remains stable up to 40 C, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 0.002 and 5 h, respectively. LICAD2 showed optimal activity at pH 6.5 and 9 for reduction and oxidation reactions, respectively, and was stable between pH 7 and 9, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 7.5 x 10(-4) and 15 h, respectively. It is a Zn-metalloenzyme with 4 Zn2+ per dimer, however, was inhibited in presence of externally supplemented Zn2+ ions. The enzyme was resistant to osmolytes, reducing agents and non-ionic detergents. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cinnamyl alcohol dehydrogenase (CAD); Metalloenzyme; Substrate specificity